Integration of ABA, GA, and light signaling in seed germination through the regulation of ABI5 - Zhao, Hongyun; Zhang, Yamei; Zheng, Yuan (Frontiers in Plant Science, 2022)
Seed germination is precisely controlled by a variety of signals, among which light signals and the phytohormones abscisic acid (ABA) and gibberellin (GA) play crucial roles. New findings have greatly increased our understanding of the mechanisms by which these three signals regulate seed germination and the close connections between them. Although much work has been devoted to ABA, GA, and light signal interactions, there is still no systematic description of their combination, especially in seed germination. In this review, we integrate ABA, GA, and light signaling in seed germination through the direct and indirect regulation of ABSCISIC ACID INSENSITIVE5 (ABI5), the core transcription factor that represses seed germination in ABA signaling, into our current understanding of the regulatory mechanism of seed germination.